Using English Comics in Improving Students’ Ability in Spoken Language - Hadi, Rifqi Nur (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Spoken language defined as a form of communication produced through articulate sounds using the vocal tract, or in some cases, through manual gestures (such as sign languages), as opposed to written language. Comics are built from a series of panels-individual frames or images-arranged in a deliberate sequence to depict the passage of time, action, or narrative progression. The purpose of the study is to prove whether or not English comics as a learning medium improves students’ speaking ability of English. Comics can be used as a medium of learning and also at the same time can be used as a medium of entertainment. The research sample was chosen from the population, specifically from a single class of 8th grade students, comprising a total of 20 students. In this study, student test results were calculated by using SPSS 23 for windows in the t-test formula to see the significance difference between pre-test and post-test. because of the effectiveness of English comics in enhancing students' speaking skill, its use might be considered a suitable medium for enhancing students’ speaking skill. This is because English comics are not only easy to comprehend, but they are also entertaining, as we are able to not only see the images but also view its attractive storylines.